The Debate about Financing Constraints of SMEs in Europe - Franziska M. Bremus (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Small and medium-size enterprises (SMEs) are highly dependent on bank financing, which is why they have been particularly hit by tighter credit conditions in the aftermath of the global financial crisis. Given that SMEs account for about 60% of value added and 70% of employment in the euro area, they are crucial for economic recovery. Consequently, several policy initiatives have been launched to alleviate SMEs' financing constraints. This Roundup gives an overview of the current debate about financing obstacles of SMEs in Europe and collects policy recommendations from the economic literature.
Keywords: 330